ECOLOGICAL AND PHYTOCENOTIC STRUCTURE OF VEGETATION COVER OF INTERFLUVE OF RIVERS RUSSKAYA AND VERBOVKA (STAVROPOL PLATEAU) - V. N. Belous; N. G. Lihovid; M. J. Kuharuk; A. A. Lihovid (Наука. Инновации. Технологии)
Introduction. Surveys of vegetation for individual steppe and forest formations are relevant for the purposes of regional typological work and the creation of a classification system of vegetation cover in the Stavropol Territory. In-depth knowledge of the structure of the vegetation cover and improvement of the typification of chorological units based on geobotanical descriptions is one of the urgent tasks of botanical and geographical surveys. The results of our research may be necessary both for the purposes of botanical geography (mapping and regionalization), and for assessing the real phytocenotic diversity of taxa of different levels. Therefore, the authors of this work set themselves the aim to identify composition and structure, diversity and specifics of tree and grass communities, the nature of their spreading across forest-steppe landscapes of the Stavropol Plateau. In the authors point of view this will make it possible to actualize the works on inventory and monographic generalization of materials on Stavropol Plateau vegetation. Materials and methods of research. The main factual resource for the work was the data collected by the authors during expeditionary reconnaissance studies on the territory of the Stavropol Plateau in 2016-2019. Coenotic surveys in key areas, collection and processing of field materials were carried out using commonly accepted geobotanical methods. A number of names of critical plant species are given in accordance with the floristic reports “Flora of the European part of the USSR”, “Flora of Eastern Europe”, “Abstract of the Caucasus Flora”. Research results and their discussion. Based on geobotanical study of the natural flora of Stavropol Plateau forest-steppe landscapes we conclude that flora of the study region within the eight key areas includes at least 227 species of higher plants. Conclusions. 1. Our studies show the diversity of vegetation across forest-steppe landscapes of Stavropol Plateau north-west borders. The region’s vegetation is peculiar both in floristic composition and in its structure, and is determined by the heterogeneity of ecotopes. In the course of field surveys, ecologicalphytocenotic features and distribution patterns of individual elements of the forest-steppe complex of the rivers Russkaya and Verbovka interfluve were established, which are primarily associated with the nature of the soil cover, the temperature regime and the water-physical properties of local soils. The article presents the phytocenotic diversity of key areas. Climax communities and herbal communities at different stages of succession are represented on plateau-like surfaces armored with a limestone slab, in the upper reaches and on the slopes of the valleys of the Russkaya and Verbovka rivers. 2. Geobotanical characterization of the current state of vegetation in study areas allows us to consider them as key units in detailing and large-scale mapping of the actual vegetation cover of the forest-steppe Stavropol territory. The collected factual data will help to reveal the structure and area ratios of the main components of the vegetation of the forest-steppe landscapes of the northwestern borders of the Stavropol Plateau. The typology of forest-steppe vegetation outlined in this report can be detailed and refined in our further work. 3. The results of our study of typical forest-steppe plant communities can have the use in large-scale mapping of vegetation of the Stavropol Upland, which will allow us to reveal more deeply some elements of the legend of a large-scale geobotanical map. 4. The studied phytocenoses contain a lot of relict, endemic and other rare species (Vitis sylvestris, Stipa pulcherrima, Astragalus demetrii, Adonis vernalis, Anemone sylvestris, Crocus reticulatus, Globularia punctata, Gypsophila glomerata, Orchis morio subsp. picta, O. purpurea, Ornithogalum arcuatum, Paeonia tenuifolia, Scilla siberica, Thymus daghestanicus, Tulipa biebersteiniana) which allows us to consider the studied landscapes as promising protected areas.